EKSISTENSI SASTRA SERIUS DALAM RANAH CYBER - Sari, Ririn Wahyu Eka; Wati, Rianna (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to examine the development and progress of literature, especially in the cyber realm. This proves that cyber literature makes it possible and easier for a writer to publish his work, both novice writers and writers. The ease of accessing literary works in the digital realm certainly makes literary works have countless numbers. Therefore, literature can be divided into two types, namely serious literature and entertainment or popular literature. Serious literature is literature that is closely related to the reality of human life, making readers guess and interpret the meaning of the reading. With the existence of literature in the cyber realm, serious literature as well as its authors are present in various platforms ranging from social media to websites and reading applications in the literature category. This research uses a descriptive qualitative method with the intention of providing a firm description and illustration accompanied by the reality and evidence of the problem under study. The results of this study show that serious literature is quite popular among readers, especially among adults and the elderly. Meanwhile, young people tend to prefer literature with popular genres because it offers stories that always end happily with a simple plot